Blood Pressure, Sexual Activity, and Erectile Function in Hypertensive Men: Baseline Findings from the Systolic Blood Pressure Intervention Trial (SPRINT). Issue 2 (14th January 2019) - Foy, Capri G.; Newman, Jill C.; Berlowitz, Dan R.; Russell, Laurie P.; Kimmel, Paul L.; Wadley, Virginia G.; Thomas, Holly N.; Lerner, Alan J.; Riley, William T.
Abstract: Introduction: Erectile function, an important aspect of quality of life, is gaining increased research and clinical attention in older men with hypertension. Aim: To assess the cross-sectional association between blood pressure measures (systolic blood pressure [SBP]; diastolic blood pressure [DBP]; and pulse pressure [PP]) and (i) sexual activity and (ii) erectile function in hypertensive men. Methods: We performed analyses of 1, 255 male participants in a larger randomized clinical trial of 9, 361 men and women with hypertension aged ≥50 years. Main Outcome Measures: The main outcome measures were self-reported sexual activity (yes/no) and erectile function using the 5-item International Index of Erectile Function (IIEF-5). Results: 857 participants (68.3%) reported being sexually active during the previous 4 weeks. The mean (SD) IIEF-5 score for sexually active participants was 18.0 (5.8), and 59.9% of the sample reported an IIEF-5 score <21, suggesting erectile dysfunction (ED). In adjusted logistic regression models, neither SBP (adjusted odds ratio = 0.998; P = .707) nor DBP (adjusted odds ratio = 1.001; P = .929) was significantly associated with sexual activity. In multivariable linear regression analyses in sexually active participants, lower SBP (β = −0.04; P = .025) and higher DBP (β = 0.05; P = .029) were associated with better erectile function. In additional multivariable analyses, lower PP pressure was associated with better erectile function (β = −0.04; P = .02). Clinical Implications: Blood pressure is an important consideration in the assessment of erectile function in men with hypertension. Strengths & Limitations: Assessments of blood pressure and clinical and psychosocial variables were performed using rigorous methods in this multi-ethnic and geographically diverse sample. However, these cross-sectional analyses did not include assessment of androgen or testosterone levels. Conclusions: Erectile dysfunction was highly prevalent in this sample of men with hypertension, and SBP, DBP, and PP were associated with erectile function in this sample.